Penggunaan Metode Cascade Aerator Untuk Penurunan Kadar Besi Dan Mangan Air Sumur Gali - Febriana Nur Aini; Narto Narto; Sri Haryanti (Poltekkes Kemenkes Yogyakarta, 2022)
Water is one of the most important components for the survival of humans and other living things. There are several parameters that must be considered in water, one of which is chemical parameters in the form of levels of iron (Fe) and manganese (Mn). Excessive levels of iron (fe) and manganese (Mn) will cause health and environmental problems so that treatment is needed to overcome these problems. The aim of the study was to determine the difference in levels of iron (Fe) and manganese (Mn) in dug well water before and after using the cascade method. Aerators. This research is a quasi-experimental research with PreTest Post Test Group Design. The object of this research is dug well water belonging to a resident in Sawit Hamlet, Panggungharjo, Sewon, Bantul. The cascade aerator used has dimensions of height for each step of 25 cm with a diameter of 30 cm and a width of 28 cm. The results of this study showed that there was a difference between the levels of iron (Fe) before and after the use of the cascade aerator method, the average decrease in iron (Fe) levels after filtering was 24.97% with a bound sig T-Test value of 0.005. There is a difference between the levels of manganese (Mn) before and after using the cascade aerator method, the average decrease in manganese (Mn) levels after filtering is 26.07% with a bound sig T-Test value of 0.010.